Transgenerational epigenetic inheritance: a critical perspective - Bird, Adrian (Frontiers in Epigenetics and Epigenomics, 2024)
Transgenerational epigenetic inheritance in humans and other vertebrates has been controversial for over 150 years and remains so. It currently depends on the assumption that the environment is able to influence the genome, in particular by altering epigenetic marks such as DNA methylation, and that these acquired markings can enter the germline and affect phenotypes in the next generation. This article will offer a critical overview of some of the evidence beneath these assumptions -particularly regarding mammals. Whilst genome sequencing increasingly strengthens the causal relationship between genotypes and organismal characteristics, the evidence for many potentially important forms of environmentally induced epigenetic inheritance remains inconclusive.